2019
DOI: 10.1002/ceat.201900021
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Tray Efficiency Estimation Method for the Fractionation System of Industrial Hydrocracking Processes

Abstract: An engineering-oriented tray efficiency estimation method for the hydrocracking fractionation system is proposed. As key parameter of the fractionation system, estimation of the tray efficiency is important and challenging due to the large computational burden given by the complexity of the fractionation system. Here, the high-dimensional tray efficiencies are screened first and divided into groups according to the spatial position. Then, an improved artificial bee colony algorithm is proposed to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…M Zhai et al, [5] analyzed a balanced flow through modification of size, runner volume, and part quality in terms of warpage, the results show runner volume and injection pressure can reduce production costs of plastic products. Wang and Sun [6] analyzed the runner imbalance in the top cover cavity and brought the product box with the Moldflow Insight 5.0 analysis, the results showed that through optimization, the imbalance of plastic fluid flow in the cavity decreased from 28.6% to 0.7%, the pressure imbalance rate injection can be decreased from 42.0% to 4.2%, and the pressure distribution in the cavity is more uniform throughout the injection-process. Raz et al, [7] modified the runner angle and balanced the injection of plastic material in the three products, the results showed that the 90º angle configuration for the runner was proven to be able to uniform the filling time of the plastic material to the three products.…”
Section: Introductionmentioning
confidence: 99%
“…M Zhai et al, [5] analyzed a balanced flow through modification of size, runner volume, and part quality in terms of warpage, the results show runner volume and injection pressure can reduce production costs of plastic products. Wang and Sun [6] analyzed the runner imbalance in the top cover cavity and brought the product box with the Moldflow Insight 5.0 analysis, the results showed that through optimization, the imbalance of plastic fluid flow in the cavity decreased from 28.6% to 0.7%, the pressure imbalance rate injection can be decreased from 42.0% to 4.2%, and the pressure distribution in the cavity is more uniform throughout the injection-process. Raz et al, [7] modified the runner angle and balanced the injection of plastic material in the three products, the results showed that the 90º angle configuration for the runner was proven to be able to uniform the filling time of the plastic material to the three products.…”
Section: Introductionmentioning
confidence: 99%